Synergistic Piezo‐ and Triboelectricity in a Novel Triglycine Sulfate/Bacterial Cellulose/Chitosan Flexible Composite Nanogenerator - Sirinya Ukasi; Kittipan Saichompoo; Chanachot Saetang; Phakkhananan Pakawanit; Satana Pongampai; Sugato Hajra; Hoe Joon Kim; Naratip Vittayakorn; Thitirat Charoonsuk (Small, 2025)
, the TENG (from the 40 wt.% TGS poled sample) powers a digital watch, showcasing practical promise. This work not only introduces TGS as a novel MEH candidate but also provides mechanistic insights into its polarization, advancing bio-hybrid nanogenerator design.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Polydiacetylene-based materials and applications